Comparative evaluation of the efficacy and safety of intra-articular administration of hyaluronic acid and glucocorticoids in the complex therapy of osteoarthritis - L. K. Peshekhonova; T. E. Kotelnikova; D. V. Peshekhonov; G. A. Kalashnik (Современная ревматология)
Improving the treatment of knee (KN) osteoarthritis (OA) remains an urgent problem.Objective: to compare the efficacy and tolerability of intra-articular (i/a) administration of long-acting glucocorticoids (GCs) and Armaviscon®Forte and Armaviscon®Platinum hyaluronates in patients with knee OA.Material and methods. From November 2019 to April 2022, we examined and treated 60 patients (26 men and 34 women, mean age 41.32±3.71 years) suffering from primary KN OA. Study participants were randomly divided into three groups of 20 patients each. In the 1st group, a longacting GCs in combination with a local anesthetic was administered once i/a into the KN, in the 2nd – Armaviscon®Forte 2.3%, and in the 3rd – Armaviscon®Platinum 3%.Patients were examined at baseline, on the 14th and 60th day after a single injection of the drug. The intensity of pain was assessed on a visual analog scale (VAS), the Lequesne index, the KOOS, WOMAC, and EQ-5D questionnaires were used. When studying tolerability, the number of adverse reactions (ARs) was taken into account.Results. By the end of the observation period in the study groups, there was a decrease in the severity of pain and an increase in functionality with positive dynamics of the Lequesne and WOMAC indices. Both hyaluronic acid drugs had a positive effect on the functional state of the joints according to KOOS, improved the quality of life according to EQ-5D. The need for non-steroidal anti-inflammatory drugs in patients of the 2nd and 3rd groups decreased down to their complete cancellation. No adverse events requiring discontinuation of therapy have been reported. The advantage of i/a administration of hyaluronates in comparison with long-acting GCs was shown.Conclusion. In real clinical practice, in patients with symptomatic OA, i/a administration of hyaluronates allows obtaining more favorable results than the use of long-acting HA.